Whip- and pinworm infections elicit contrasting effector and distinct regulatory responses in wild house mice. Issue 8 (July 2022) - Zhang, Hongwei; Bednář, Lubomír; Heitlinger, Emanuel; Hartmann, Susanne; Rausch, Sebastian
Graphical abstract: Highlights: Nematode-infected wild house mice reflect type-1 vs type-2 immune bias seen in experimental whip- and pinworm infections. Th1 expansion is accompanied by a rise in IL-10+ Th1 cells irrespective of infection status. Elevated type-2 activity in pinworm infection is paired with expanded regulatory T cells. Abstract: Infections with high doses of intestinal nematodes result in protective immunity based on robust type 2 responses in most mouse lines under laboratory conditions. Here, we report on cellular responses of wild house mice from northern Germany. We detected robust Th1 responses in wild house mice naturally infected with the whipworm Trichuris muris . In contrast, mice infected with pinworms ( Syphacia, Aspiculuris ) reported type-2 activity by elevated IgG1 levels and eosinophil counts, but also harbored high frequencies of Foxp3+ regulatory T cells, suggesting that natural whip- and pinworm infections induce distinct immunoregulatory as well as effector profiles.